1994
DOI: 10.1139/e94-119
|View full text |Cite
|
Sign up to set email alerts
|

Geochronological constraints on late Archean magmatism deformation and gold–quartz vein mineralization in the northwestern Anialik River greenstone belt and igneous complex, Slave Province, N.W.T.

Abstract: Three phases of the Anialik River igneous complex (ARIC) give U–Pb zircon ages in the range −2705–2683 Ma, and three units from the adjacent northwestern Anialik River greenstone belt (ARGB) give ca. 2678 Ma ages. Titanite from unsheared ARIC rocks crystallized during localized metamorphism and deuteric alteration between 2693 and 2683 Ma. Hydrothermal titanite in wall rocks to gold-mineralized shear zones crystallized during early shear zone development (2670 ± 1 Ma) and was subsequently locally altered to ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
4
19
0
Order By: Relevance
“…The darker colour and higher U concentrations of these fractions may indicate primary igneous titanite, as described for samples elsewhere by Verts et al (1996), Stone (1998), andFrost et al (2000). However, Abraham et al (1994) suggested that Th/U ratios of -1 were characteristic of metamorphic titanite. Primary igneous titanite has not previously been documented in the norite of the SIC and is uncommon in mafic rocks in general (Frost et al 2000).…”
Section: U-pb Titanite Agementioning
confidence: 67%
“…The darker colour and higher U concentrations of these fractions may indicate primary igneous titanite, as described for samples elsewhere by Verts et al (1996), Stone (1998), andFrost et al (2000). However, Abraham et al (1994) suggested that Th/U ratios of -1 were characteristic of metamorphic titanite. Primary igneous titanite has not previously been documented in the norite of the SIC and is uncommon in mafic rocks in general (Frost et al 2000).…”
Section: U-pb Titanite Agementioning
confidence: 67%
“…2) comprises rocks of the ca. 2.71 -2.68 Ga (U-Pb zircon ages; Abraham et al 1994) ARIC and the northwestern arm of the Anialik River greenstone belt (ARGB). This area is covered by the Hepburn Island map area (76 M) and has been the subject of a number of reconnaissance and lithostructural mapping projects (O'Neill 1924;Fraser 1964;Tirrul and Bell 1980;Yeo et al 1984;Jackson et al 1985), the most recent being a 1 : 30 000 scale Geological Survey of Canada MDA-NATMAP project (Relf 1993 and references therein).…”
Section: Geological Settingmentioning
confidence: 99%
“…The general geology of the Arcadia Bay area (Fig. 3) has previously been described (Abraham 1989), and a brief description of the major lithologies is given below; ages are quoted from Abraham et al (1994).…”
Section: Major Lithologiesmentioning
confidence: 99%
See 2 more Smart Citations